Contribution of Teachers in Achieving the Goals of Basic Education: A Literature Review on Best Practices and Challenges - Rita, Novia; S, Neviyarni; Irdamurni, Irdamurni (Postgraduate School, Universitas Negeri Padang, 2023)
Teachers play a crucial role in achieving the goals of basic education. This article aims to conduct an in-depth literature review on the contribution of teachers in realizing the objectives of basic education by identifying the best practices employed by teachers and analyzing the challenges they face in reaching these goals. The article is a descriptive-analytical research study that collects data through searching and analyzing various relevant articles, journals, and scholarly literature. The data is gathered by searching literature through academic databases and digital libraries. Relevant articles are selected based on predetermined inclusion and exclusion criteria. Subsequently, the data is systematically analyzed, and significant findings are identified. The research findings indicate that teachers have significant contributions in achieving the goals of basic education. Teachers utilize innovative teaching methods, consider individual student differences, provide constructive feedback, collaborate with students and parents, and build positive relationships with students. However, there are challenges, including limited resources, student individual differences, and time constraints and high workload.